2016
DOI: 10.13080/z-a.2016.103.022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fungicides in sugar beet crops

Abstract: Cercospora and ramularia leaf spot are the most damaging fungal diseases of sugar beet in Europe. The aim of the current study was to evaluate the severity of fungal diseases and the efficacy of various fungicides and their doses in sugar beet crops in Lithuania. A short-term field experiment was carried out in 2012 and 2013 at Rumokai Experimental Station, Lithuanian Research Centre for Agriculture and Forestry on a moderately heavy loam HapliEpihypogleyic Luvisol (LVg-p-w-ha). Fungicides Impact (a.i. flutria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Fungicides are well known for their role in disease control (McGrath2004). Finally, Avižienytė et al (2016) found that the fungicide Opus is the most effective against powdery mildew when treated twice. Various active ingredients of the fungicides had insignificant effects on sugar beet yield and sucrose content in the roots.…”
Section: Resultsmentioning
confidence: 99%
“…Fungicides are well known for their role in disease control (McGrath2004). Finally, Avižienytė et al (2016) found that the fungicide Opus is the most effective against powdery mildew when treated twice. Various active ingredients of the fungicides had insignificant effects on sugar beet yield and sucrose content in the roots.…”
Section: Resultsmentioning
confidence: 99%
“…Total soluble solids % was significantly enhanced when handling beet plants of Rhizoctonia and Trichoderma in contrast with the control of the 1st and 2nd growing seasons. Dovil‫כ‬ et al 34 observed the small impact of fungicides on sugar beet yield and sucrose quantity. The Trichoderma sp.…”
Section: Discussionmentioning
confidence: 99%
“…The application of foliar fungicides in integrated sugar beet cultivation beneficially affects not only the health of leaves and the leaf area index but also the yield and technological quality of roots [22][23][24]. Therefore, and also in view of the preference for choosing agricultural technologies that accord with the principles of integrated cultivation, long-term research was carried out on the impact that various fungicidal protection methods had on sugar beet root yields.…”
Section: Introductionmentioning
confidence: 99%